1995
DOI: 10.2166/wst.1995.0572
|View full text |Cite
|
Sign up to set email alerts
|

Removal and inactivation of cryptosporidium oocysts by activated sludge treatment and anaerobic digestion

Abstract: To determine the fate of Cryptosporidium parvum oocysts during wastewater treatment, a model of an activated sludge treatment plant was designed with a flow of 17 ml/min and a detention time of 6 hours. Samples of raw sewage were seeded with oocysts and primary and secondary effluents were analyzed for C. parvum using an immunofluorescent technique. To compare removal efficiencies of oocysts by various wastewater treatment processes, raw sewage, activated sludge, trickling filter and biodisc effluents were see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…2005). Additionally, in mesophilic anaerobic digestion, reduction of Cryptosporidium is reported to be 2-3 logio (Stadterman et al 1995), substantially more than observed for C. perfringens in this study. Taken together, these reports support our data and suggest that C perfringens is a poor indicator of the inactivation of enteric organisms in biosolids.…”
Section: Pathogen Die-offcontrasting
confidence: 43%
“…2005). Additionally, in mesophilic anaerobic digestion, reduction of Cryptosporidium is reported to be 2-3 logio (Stadterman et al 1995), substantially more than observed for C. perfringens in this study. Taken together, these reports support our data and suggest that C perfringens is a poor indicator of the inactivation of enteric organisms in biosolids.…”
Section: Pathogen Die-offcontrasting
confidence: 43%
“…The numbers of Cryptosporidium, Giardia and Ascaris ova in effluent were less than 100 organisms/L. The removal of helminths in wastewater treatment occurs in the activated sludge system by means of enmeshment into the biofloc during secondary settling (Stadterman et al, 1995). The mechanism of helminths removal through sedimentation in activated sludge was believed to take place through the hindered-settling region in which highly concentrated flocculated materials form a ''blanket'', which acts as a filter to remove suspended particles.…”
Section: Removal Of Protozoan Pathogens and Helminthsmentioning
confidence: 99%
“…The mechanism of helminths removal through sedimentation in activated sludge was believed to take place through the hindered-settling region in which highly concentrated flocculated materials form a ''blanket'', which acts as a filter to remove suspended particles. The lack of a significant correlation between reductions in turbidity and removal of helminths following primary settling was more likely to be due to the lack of a settling blanket formation (Stadterman et al, 1995). Protozoan pathogens are predators in the wastewater treatment ecosystem, and since their specific gravity is similar to that of parasite eggs, most protozoa are removed through attachment to activated sludge flocs and subsequent settling.…”
Section: Removal Of Protozoan Pathogens and Helminthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological filter is particularly suited for treatment of moderate BOD load or as a polishing step in combination with other techniques (WEF 1996, Stadterman 1995and Parker 1996. It could also be used, in some cases, as a roughing filter for a high-strength wastewater (USEPA 2000).…”
Section: Introductionmentioning
confidence: 99%